Perlindungan Hukum Terhadap Kurir Dalam Sistem Cash On Delivery - Helmi Djardin; Merry Tjoanda; Muchtar Anshary Hamid Labetubun (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: The Cash On Delivery method is often used by the public in online purchases, the lack of public knowledge of the Cash On Delivery payment system creates new problems when the purchase of goods does not match, the buyer does not want to pay for his order and threatens and violence against the courier.Purposes of the Research: Analyze and examine how the rights and obligations between the parties in online transactions with the Cash On Delivery system and how the legal protection of couriers in the Cash On Delivery system. Methods of the Research: This research is included in normative legal research, namely research examining positive legal provisions, legal principles. Legal principles and doctrines to answer the legal issues faced.Results of the Research: In buying and selling online using the Cash On Delivery system, there are parties involved, namely the marketplace, sellers, consumers, and shipping service companies (couriers). This sale and purchase creates rights and obligations that must be fulfilled, in this case there are no regulations that specifically regulate the protection of couriers, but the employer company is required to provide protection to its workers. The company is responsible for occupational safety and health, including work accidents.